Fast handover support in a WLAN environment challenges and perspectives. - Dimopoulou, L. (IEEE Network : the magazine of global information exchange)
While handover management has traditionally used radio-technology-specific mechanisms, the need for integration of this diverse network environment has obviated the "push" of the handover functionality to the generic IP layer that serves the rendezvous point of underlying technologies. In this context, we study and analyze the implications of the link-layer agnostic operation of IP handover control on handover performance, having as a reference the fast mobile IPv6 protocol. We show that the behavior of the protocol (i.e., whether a reactive or proactive operation will be executed) is highly dependent on the timely availability of link layer information. A non-exhaustive list of generic link-layer triggers used for this purpose, as identified by the IEEE 802.21 WG, is also presented. Last, we apply this generic framework to a WLAN environment running fast mobile IPv6 and study the improvements in fast handoff support.